Pengaruh Model Pembelajaran Joyful Learning Terhadap Minat Belajar Siswa Di MTsN 3 Surabaya - Hanani, Aulia; Yuliastutik (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Teacher creativity in carrying out learning activities is an important thing to increase students' interest in learning. Teaching creativity can be in the form of using fun learning models. In this case, fun learning is not only to make it easier for students to understand the material presented, but to help students in increasing their interest in learning so that they can get maximum learning results. \ The purpose of this research is to determine whether there is an influence of fun learning models on student learning interests. This study uses a quantitative research approach with a descriptive type of research using data collection techniques in the form of documentation and questionnaires. While the data that has been obtained is analyzed using pearson product moment with the help of the Statistical Package for the Social Sciences application. The results showed that: (1) the implementation of the joyful learning learning model in MTsN 3 can be categorized as "high" because the average joyful learning variable is in the interval 31-34 with a percentage of 27.5%, (2) student learning interest in MTsN 3 Surabaya through joful learning has an average of 32.7 which is at the interval of 35%. So it can be concluded that students' interest in learning in MTsN 3 Surabaya is "high", (3) From the results of the hypothesis test conducted, a pearson correlation value of (0.564) was obtained where the results were greater than the table R of (0.316). Based on the results of decision making that if the value of person correlation > R table, it can be concluded that there is a significant influence between the implementation of the joyful learning learning model on student learning interest